On the deviant age-crime curve of Afro-Caribbean populations: The case of Antilleans living in the Netherlands - Jennissen, Roel (American journal of criminal justice, 2014)
The crime figures among Antilleans (people from islands in the Caribbean Sea) residing in the European country of the Netherlands remain high for offenders in their twenties and thirties, unlike other major ethnic groups residing in the Netherlands. The aim of this study is to get a better insight into the backgrounds of the deviances in the shape of the age-crime curve for this ethnic group. The research comprises a quantitative analysis of data regarding people who are registered as an offender in the Netherlands. This study has found indications that the high level of broken families might be related to comparatively high rate of offenders among adult Antillean men up to approximately 45 years.